IMPLEMENTASI STRATEGI KOMUNITAS PEMUDA HIJRAH DALAM DAKWAH DAN SYIAR ISLAM DI MEDIA SOSIAL - Irna Qurani (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
The development of contemporary da'wah in Indonesia is marked by the phenomenon of the rise of hijrah communities in various cities. The Hijrah Youth Movement Community is an Islamic community that embraces all young people who have migrated in order to strengthen friendship and draw closer to Allah SWT. Pemuda Hijrah, better known as